ANALISIS SEKTOR BASIS PERTANIAN DALAM PERTUMBUHAN EKONOMI DI SUMATERA UTARA - Elvin Desi Martauli; Suranta Sembiring (JURNAL AGROTEKNOSAINS, 2023)
This study aims to analyze the agricultural sub-sector in North Sumatra Province which is the basis for economic growth and to analyze the factors that cause changes in the position of the agricultural sector in North Sumatra Province. This type of research was a case study with a quantitative description approach. The data used and processed were secondary data from 2018 to 2022. The data analysis techniques used in this research are Location Quotient (LQ) analysis, Dynamic Location Quotient (DLQ), a combination of LQ and DLQ and Shift Share. Based on the results of the analysis, it was found that the agricultural sub-sector which was the basis sub-sector for the economy of North Sumatra Province during the 2018-2022 research year, namely food crops, horticulture, livestock, plantations and fisheries. Factors that cause changed in the position of the plantation sub-sector are economic structure factors.